Puzzling questions about the solar system - Gardner, Martin, 1914-2010.; Gardner, Martin, 1914-2010.; Schroeder, Ted (Mineola, N.Y. : Dover Publications, 1997)
Brief introductions to space flight and the various bodies in the solar system are followed by sections of related puzzle questions. Answers are given at the back of the book.
Rev. and enl. ed. of: Space puzzles. 1971.
Includes index.
Keywords: Solar system -- Juvenile literature; Solar system